Throwing velocity in elite water polo from different areas of the swimming pool - Abraldes, J. A.; Ferragut , C.; Rodrigue, N.; Alcaraz, P. E.; Vila, H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study is threefold: 1) To identify the throwing velocity during a match; 2) to identify possible differences in throwing velocities between male and female players; 3) to determine shot velocity from different zones of the court during real competition. We analyzed the water polo world championship. In order to evaluate the precise strength production, a radar gun was used. A one-way analysis of variance was applied (ANOVA) to study differences among playing areas. In addition, a t-Test for repeated measures was employed to compare different groups. This study identifies three major zones of goal shot. We identified the highest throwing velocity zones and the zones with highest shot number. In addition, the results show that the penalty shot is the fastest shot.